Sistema informático de monitoreo del historial académico de los estudiantes del instituto de idiomas de la ESPAM MFL - Quijije Antón, Mario Ramón (2013)
The main objective of this work was to create a system to monitor academic process at the Language Center of the ESPAM MFL, to streamline and automate the management of student academic records. The application allows the user to perform registration of students and take their grade in an orderly manner. For the execution of the application methods like inductive-deductive and SCRUM were used. Information was collected to define the requirements and architecture of the system, then drew up the database that was attached to the treatment and handling of information through a database manager and an integrated development environment (IDE) which allowed interfacing and application functionalities. For validation, the system was analyzed by the director of the Language Center, this way it was found the proper functioning and obtained results in a favorable acceptance for use and implementation.